ETIKA KEWARGANEGARAAN DIGITAL DAN ANCAMAN DEEPFAKE: ANALISIS KASUS VIDEO PIDATO BAHASA MANDARIN TOKOH PUBLIK DI INDONESIA - Dara Ayodya Santoso; Elok Wilujeng Hanifatuz Zahra; Giar Anita Ningrum; Ratulafika Aisya Shofiyatudin; Annisa Rahmadyah; Aida Sabilillah (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
The development of Artificial Intelligence (AI) technology poses a threat to the ethics of digital citizenship through the spread of disinformation and manipulation of public opinion, especially deepfakes. This study aims to analyze the threat of AI-based video manipulation to digital citizenship ethics and the importance of digital literacy through the case of a video of President Joko Widodo giving a speech in Chinese. The research uses a qualitative method with a descriptive approach. Data sources were obtained from deepfake videos, social media, scientific journals, and news. Data collection was carried out through digital observation and literature review, while data analysis used qualitative descriptive analysis with source triangulation. The results of the study show that deepfakes can affect public trust and increase the spread of fake news. Therefore, strengthening digital literacy, digital ethics, social media surveillance, and government regulations is needed to prevent the spread of AI-based manipulative content.